2011
DOI: 10.1126/science.1203698
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Retrieval Practice Produces More Learning than Elaborative Studying with Concept Mapping”

Abstract: Karpicke and Blunt (Reports, 11 February 2011, p. 772) reported that retrieval practice produces greater gains in learning than elaborative studying with concept mapping and concluded that this strategy is a powerful way to promote meaningful learning of complex concepts commonly found in science education. We question their findings on methodological and epistemological grounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 5 publications
(2 reference statements)
1
18
0
Order By: Relevance
“…To construct structured knowledge different teaching methods promoting meaningful learning are proposed (Ivie, 1998;Karpicke, 2012;Nesbit and Adescope, 2006). Among them, recent work addressed the question of which of the learning methods-active retrieval or CM elaboration-is the most powerful to achieve meaningful learning (Karpicke and Blunt, 2011;Mintzes et al, 2011). Retrieval is a process using available cues to actively reconstruct knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…To construct structured knowledge different teaching methods promoting meaningful learning are proposed (Ivie, 1998;Karpicke, 2012;Nesbit and Adescope, 2006). Among them, recent work addressed the question of which of the learning methods-active retrieval or CM elaboration-is the most powerful to achieve meaningful learning (Karpicke and Blunt, 2011;Mintzes et al, 2011). Retrieval is a process using available cues to actively reconstruct knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Training in the use of knowledge maps, including developing a map, is an important condition in achieving these benefits (O'Donnell et al, ; cf. Mintzes et al, ). Similarly, causal maps enable group members to literally see what is discussed (Shields, ; Bryson et al, ).…”
Section: The Impact Of Model Usementioning
confidence: 99%
“…Studies on the benefit of retrieval practice have only recently become more common, yet several have shown that there are significant mnemonic effects (7,15). However, a major limitation to these studies, as pointed out by Mintzes et al (9), is that this research was carried out in a psychology laboratory setting rather than as an embedded intervention in a real undergraduate course.…”
mentioning
confidence: 99%